Design of soft robot for maneuvering in tight spaces - Tan, Zitang (2023)
Soft robotics is an emerging field that combines engineering and materials science. Soft robots, as compared to typical rigid robots, are built with flexible and pliable materials, allowing them to adapt to complex and dynamic surroundings. It provides unique answers to difficulties that traditional robotics cannot handle by imitating the softness and adaptability of natural organisms. This project demonstrates the fundamental principles, design strategies and the application of soft robot, such areas include healthcare, exploration and also human-robot interaction. This project narrows down and focuses on the design of soft robot for maneuvering in tight spaces. Pneumatic actuation and pleated segment structure is chosen to design the soft robot. Where the material chosen was Ecoflex. All of these considerations were made because they are easy to use and applicable to build a simple maneuverable soft robot. Finite Element Modelling was performed to compare different types of soft robot structures having different bending motion as three different types of structures built to obtain the optimal design for the soft robot. In the end of the experiment, it can be observed that higher frequency applied to the solenoid valves will lead to higher voltage that able to apply to the micro pumps and causing the distance travelled by soft robot to be further in 60 seconds. Among the 3 types of different design of soft robot, the fully covered type is found to be more stable and not break easily. Whereas the unfully covered with thicker wall, which is the best design in this project travels further and forms a better bending shape.